2021
DOI: 10.15835/nsb13210921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water erosion on the properties of forest soils

Abstract: The research work was conducted on eroded soil in the Keroua forest of Saida, Algeria, whose objective is to know the changes in the physicochemical and biological properties of forest soils subjected to the effect of water erosion. The samples were taken to a depth between 0-10 cm in each zone (eroded zone and control zone). Our results show that the biological properties are the most affected by water erosion where there was a significant decrease in basal respiration and microbial biomass, which had a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The altitudes are high (1,000 m on the average) [ 14 ] . The types of soils are poorly evolved, calcareous brown soil, rendzine, fersiallitic, calcomagnesium, and isohumic brown soils [ 15 ] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The altitudes are high (1,000 m on the average) [ 14 ] . The types of soils are poorly evolved, calcareous brown soil, rendzine, fersiallitic, calcomagnesium, and isohumic brown soils [ 15 ] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Mathieu (2020) indicated that overgrazing leads to plant destruction and other related issues, mainly soil grading as roots grow slowly in compacted soil, altering the formation and the stability of aggregates which reduce gas soil exchanges, permeability and capillary properties and results in the soil becoming sensitive to erosion (waterborne and wind). Deforestation and overgrazing are usually mentioned as the leading causes of soil erosion (Lahmar & Ruellan, 2007;Allam et al, 2021;Aouadj et al, 2023b) which may reduce or modify, in the long term, the returning of soil microbial properties. According to Six et al (2004), aggregation dynamics, organic matter composition and stabilization along with soil biological activity are related.…”
Section: Analysis Of Main Factors Of Correlation Between Chemical And...mentioning
confidence: 99%
“…In Romania, the area occupied by black locust has increased continuously [25,26]. Depending on the favorable ecological conditions, black locust could contribute in the same way as other forest species or by supplementing them, ensuring the multiple functions of the forest at local, zonal, regional, national or global levels [27][28][29][30][31][32][33][34]. The quality of the seeds is the first condition for the afforestation to be successful and for the resulting forests to fulfil their numerous functions; i.e., production, protection, ecological, cultural, educational, etc.…”
Section: Introductionmentioning
confidence: 99%